Ruská filozofie 19. a začátku 20. století Čítanka antropologicky zaměřených textů ruských filozofů idealistické orientace - Dohnal, Josef (Masaryk University Press, 2023)
Title in English: Russian Philosophy of the 19th and Early 20th Century: A reader of anthropologically oriented texts by Russian philosophers of idealist orientation The textbook contains medallions of nine selected Russian philosophers of the 19th and early 20th century - P. Ya. Chaadaev, N. A. Berdyaev, S. N. Bulgakov, N. F. Fyodorov, P. A. Florensky, S. L. Fank, K. N. Leontyev, V. S. Solovyov and L. N. Tolstoy. In the next section, the texts of these philosophers are presented in the original Russian so that readers can become familiar with the basic underpinnings of their philosophical concepts. The textbook is intended for students of Russian studies, philosophy and humanities in general at the faculties of philosophy and education in the Czech and Slovak Republics, as well as for a wider circle of those interested in Russian idealist philosophy.